Monsoon Precipitation, Economy and Wars in Ancient China - Zhang, Jixiao; Zhou, Xin; Jiang, Shiwei; Tu, Luyao; Liu, Xiaoyan (Frontiers in Earth Science, 2020)
Northern China, particularly the Yellow River Basin, which is the birth place of Chinese civilization and has been the political center throughout most of China’s history, is an ideal region for studying the response of human activities to climate change. However, studies on links between climate change and variations in earlier civilization are limited due to the scarcity of macroscale monsoon precipitation records. In the present study, a ~4,000-year record of monsoon precipitation, which represents average rainfall in large areas in northern China, was reconstructed from sediments in Northern Yellow Sea Mud (NYSM). The record shows high monsoon precipitation from ~4,000–~2,500 BP, ~1,350–~750 BP and during the past ~250 years. In general, our record of monsoon precipitation exhibits trends similar to the percentages of planted Poaceae pollen in lake sediments and the Chinese economic index, contrasting with the frequency of wars over the past 2,000 years. We postulated that, in the agricultural society of ancient China, low monsoon precipitation in northern China may be an important factor that cause reduced agricultural production, declined economy and even the occurrence of wars.